Global trends in countries' perceptions of the Belt and Road Initiative - Alicia García-Herrero; Robin Schindowski (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
Since China's Belt and Road Initiative (BRI) was announced almost a decade ago, circumstances in global politics have changed radically. The trade war between the United States and China, and most recently the Covid-19 pandemic have caused a partial reshuffling of the international economic architecture. At the same time, China has become stronger and more self-confident, more innovative and more embedded in global value chains. Under the framework of the BRI it has become the world's largest official creditor in 2017. As of recently, an increasing number of countries have fallen into debt distress, some of which have received substantial investment from China. The question is then how the image of the BRI has evolved as these conditions have shifted. Drawing on global media reports, we conduct an analysis of the sentiment towards China's Belt and Road Initiative across geographies and of how this sentiment has evolved over time.
urn:nbn:fi-fe2023052245907
Keywords: 330; China; Belt and Road Initiative; sentiments